VANET Coverage Analysis for GPS Augmentation Data in Rural Area. Issue 30 (2016) - Speth, Thomas; Riebl, Raphael; Brandmeier, Thomas; Facchi, Christian; Jumar, Ulrich; Al-Bayatti, Ali H.
Abstract: Enhanced position accuracy is key for modern navigation systems, location based services and applications based on Inter-Vehicle Communication (IVC). Position data are the foundation for deriving vehicle trajectories used for assessing a situation's criticality in vehicle safety. Thus, especially Advanced Driver Assistance Systems (ADASs) and integral safety applications benefit from nearby vehicles spreading their positions periodically with high accuracy. Positioning based on Global Navigation Satellite System (GNSS) measurements can be enhanced by established Cooperative Positioning (CP) methods like Real-Time Kinematic (RTK) and Differential GNSS (DGNSS). Conventional CP relies on positioning correction data from a third party, whereas this paper introduces a self-sufficient CP system based on Precise Point Positioning (PPP) and Vehicular Ad-Hoc Network (VANET) technology requiring no infrastructure. Furthermore, the data dissemination process and achievable coverage are analysed by a simulation study for a rural area in Bavaria, Germany. For this purpose, the simulation employs the European IVC protocol stack ITS-G5. While the general feasibility of this CP approach could be assured, some remaining issues regarding employed network protocols were discovered as well.